Urban Andes Design-Led Explorations to Tackle Climate Change. - d'Auria, Viviana (Lap Ser., 2022)
Climate change in the Andes is affecting the relation between urban development and the landscape. Design-led explorations are reframing landscape logics and urbanisation patterns within the Cachi River Basin of Ayacucho, Peru. A co-production of students, researchers and designers, the book suggests alternative futures, crossing scales of landscape systems to new settlement typologies. 'Urban Andes' marks the start of the new series 'LAP' on innovative design research in architecture, urbanism, and landscape. It is the result of a two-year collaboration (2018-2020), initiated by the CCA in cooperation with KU Leuven and various partners, including local organisations and the VLIR-UOS.